Perception of facial profiles: influence of female sex hormones and personality traits. (21st September 2016) - Jovic, T.; Pavlic, A.; Varga, S.; Kovacevic Pavicic, D.; Slaj, M.; Spalj, S.
Structured Abstract: Objectives: The observational study investigated whether women's perception of the facial profile is related to changes in sex hormones during the menstrual cycle and under the influence of personality traits. Setting and sample population: Participants were heterosexual Caucasian normally menstruating women not using oral contraceptives ( N = 30, aged 20–44 years). Material and methods: The profile attractiveness was assessed by grading of thirteen men's and women's Caucasian profile distortions by a visual analogue scale (0 = least to 100 = most attractive) in the non‐ovulating phase and ovulating phase of the menstrual cycle. Male profiles were graded twice—in social and emotional contexts. Personality traits were assessed by Big Five Inventory. Results: The most attractive male profiles in both phases and contexts were a straight profile or mild lip retrusion. According to cluster analysis, non‐ovulating females distinguish skeletal from dentoalveolar alterations; however, maxillary retrognathism was considered to be closer to an attractive profile, which were resulting from dentoalveolar manipulations only. Ovulating females, when considering emotional relationship, exhibit lowest preference for males with convex profiles and extreme concave profile, while they consider males with slightly prominent chins due to maxillary retrognathism, mandibular prognathism or pronounced lip retrusion closer to the most attractive males. No clear patterns of influence of personality traits were detected. Moderate lip protrusion was the most attractive female profile in ovulating and straight profile in non‐ovulating phase. Conclusion: The favorable profiles, on average, are the same regardless of the female hormonal status and personality traits.